Development Of Flipbook On The Regulation Process In Plants For Senior High School With Independent Curriculum - Ambarwati, Dewi Sekar; Filayani, Muhammad Iqbal (Biopedagogia, 2025)
An example of utilizing technology in learning is the transition from conventional learning resources like print to digital ones like flipbooks. Choosing digital learning resources is considered advantageous compared to print learning resources because digital resources are more engaging and interactive, thus capturing students' interest in learning. In this study, the development of a flipbook on the regulation process in plants using the ADDIE development model was conducted. This development model consists of 5 stages: analysis, design, development, implementation, and evaluation. This research aims to understand the process of developing the flipbook learning resource and to assess its feasibility. Feasibility testing was performed through expert validation, considering aspects such as content, media, design, and language. The results of this study show a validity score of 82.6% from media experts, 92.3% from content experts, and 78% from subject teachers. With these scores, the flipbook is concluded to be valid and engaging, thus suitable for use in learning activities.Keywords:  flipbook, learning sources, ADDIE, Biology, Independent Curriculum